Evaluation of Disposal Stability for Cement Solidification of Lime Waste - Shon, Jong-Sik; Lee, Hyun-Kyu; Kim, Gi-Yong; Kim, Tack-Jin; Ahn, Byung-Gil (Materials, 2022)
The Korea Atomic Energy Research Institute (KAERI) obtains UO2 powder using the ammonium uranyl carbonate (AUC) wet process. Hydrated lime (Ca(OH)2) is used to neutralize liquid wastes produced from the AUC process, and the resulting byproduct is known as lime waste. The purpose of this study is to determine optimum operating conditions for cementation of radioactive lime waste produced from the AUC process, and to evaluate the structural stability and leaching stability of cement waste form. The waste acceptance criteria (WAC) of a waste disposal facility in Korea were used to evaluate the cement waste form samples. The maximum lime waste content guaranteeing the shape stability of cement waste form was found to be 80 wt.% or less. Considering the economic feasibility and error of the cementation process, the optimum operating conditions were achieved at a lime waste content of 75 wt.% and a water-to-cement (w/c) ratio of 2.0. The compressive strength of cement waste form samples prepared under optimal operating conditions was 61.4, 76.3, and 61.0 kgf/cm2 after the thermal cycling test, water immersion test, and irradiation, respectively, satisfying the compressive strength of 35.2 kgf/cm2 specified in WAC. A leaching test was performed on the samples, and the leachability indexes (LX) of Cs, Sr, and Co nuclides were 7.63, 8.02, and 10.89, respectively, which are all higher than the acceptance criterion of 6. The results showed that the cement waste forms prepared under optimal operating conditions satisfied the WAC in terms of structural stability and leaching stability. As such, the proposed cement solidification method for lime waste disposal can be effective in solidifying lime waste powder produced during the neutralization of liquid wastes in the AUC process.